Selective cerebral perfusion for reduced cerebral blood flow during debranching thoracic endovascular aortic repair - Satoshi Sakakibara, MD; Takashi Yamauchi, MD, PhD (Journal of Vascular Surgery Cases and Innovative Techniques)
A 69-year-old man with chest pain was diagnosed with acute type B aortic dissection with the entry tear located at distal arch and a distal aortic arch aneurysm. Therefore, we performed debranching thoracic endovascular aortic repair 2 weeks after type B aortic dissection onset. First, the graft was anastomosed to bilateral axillary arteries. After clamping the left common carotid artery (LCCA), the regional cerebral oxygen saturation decreased notably. Therefore, we used selective cerebral perfusion using a roller pump with a filter to prevent embolization, a 24F sheath inserted into the left common femoral artery (drainage cannula), and a balloon perfusion catheter inserted into the LCCA (arterial cannula). This technique improved the rSO2 and was continued during anastomosis of the graft to the LCCA. Thoracic endovascular aortic repair was performed after debranching from the right axillary artery to the LCCA and left axillary artery. The patient was discharged 7 days postoperatively without cerebral complications.